Residents willingness to pay for conservation of green spaces and amenities at urban forest Bukit Nanas, Kuala Lumpur - Azman A. Rahman,; Faten Naseha Tuan Hussain,; Shaharuddin Mohamad Ismail, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
Greenery plays a key role in urban ecosystems could generate a wide range of services and amenities. They provide residents with outdoor recreational opportunities and contacts with nature to nurture a harmonious people–environment relationship healthy living environment. Cities of Kuala Lumpur have a growing demand for green spaces, due to growth in populations, improved quality of life, increased leisure time, and rising environmental awareness and expectation. Unfortunately, the recent rapid pace of urban expansion and redevelopment have eradicated or degraded some existing urban green spaces and failed to preserve natural pockets and corridors in large-scale sprawling into green fields. The main aim of this study is to determine the willingness to pay (WTP) and the residents’ value of urban green space in Kuala Lumpur city. The results show that 60% of the residents are willing to pay between RM 2 to RM 5 per year for the conservation of the urban green space. The results also indicated that most of the respondents feel responsible towards the existing urban green space and concern towards amenity in Bukit Nanas Forest Reserve.